Aqueous Oxidation of Sodium Phosphite by Dissolved Oxygen Using Sulfur Dioxide in in a Catalytic Raction - Satoshi Yamashita; Takafumi Kondo; Noboru Masuko (The Minerals, Metals and Materials Society, 2000)
"Aqueous oxidation of phosphite ions to phosphate ions with dissolved oxygen was examined at 80° C and pH 4.5 mainly from the stichiometric point of view. Dissolved oxygen alone can not oxidize sodilim phosphite in aqueous solution, but when sulfur dioxide is coexistent, cooperative oxidation for both sulfite and phosphite can occur in aqueous solution. Sulfur dioxide itself is well known as a reducing agent, but it also reacts as an oxidation-promoting agent for other species under a certain condition. So sulfur dioxide is· a promising cheap reagent for waste phosphite processing.IntroductionIn a liquid-phase oxidation reaction using the dissolved oxygen gas, the eoexistence of a copper salt is required generally. Recently, it was reported that the oxidation reaction progressed by using mixed gas of sulfur dioxide and oxygen without the copper catalysis, and the attention has been collected1·3). The present authors also noticed the phenomenon since the early time and have been studying on the reaction mechanism of sulfur dioxide in liquid phase oxidation 4l. It was found that; by using the SO2-O2 mixed gas, the oxidation of phosphite ions to phosphate ions proceeded efficiently in sulfuric acid solutions. In the present report, the applicability of SO2-O2 mixed gas as a cheap oxidizing agent to the industrial processing of the waste solution of electroless nickel· plating is investigated. It is well known that the sulfur oxide dissolved in aqueous solution is oxidized ·by the oxygen in the air to sulfuric acid according to the following equation"